Developing educational tools for One Health: Transformative strategies for zoonosis prevention - Lorena D. M. S. Maia; Breno O. L. Ramos; Rebecca F. dos Santos Martins; Daniel L. de Miranda Cravo; Érica L. M. Araújo; Cíntia G. S. Diniz; Camila S. F. de Oliveira (Health Education Journal, 2026)
Objectives: This study aimed to describe the development, implementation, and material costs of four low-cost educational strategies for zoonosis prevention and One Health education in schools. Design: Methodological, qualitative, and descriptive study. Setting: Public elementary schools in Contagem, Minas Gerais, Brazil. Method: Four educational strategies were developed for elementary school children: board games, theatre, group discussions, and videos. The strategies addressed sporotrichosis, leishmaniasis, Rocky Mountain spotted fever, and rabies. Materials, implementation procedures, practical adaptations, and costs were described. The activities incorporated elements of transformative education, including game-based learning, role-play, mediating questions, motivational phrases, encouragement, problem contextualisation, and collaborative problem-solving. Descriptive observations, facilitators’ qualitative impressions, and spontaneous student comments were used to contextualise the implementation process. Results: The strategies created opportunities for student participation, peer interaction, and collaborative engagement during classroom activities. Their interactive, playful, visual, and contextualised elements supported active participation and discussion of One Health–related topics. The estimated production costs were low, and the materials were feasible, accessible, and adaptable to different school contexts. Conclusion: This study provides a practical description of low-cost and replicable educational strategies for zoonosis prevention and One Health education. The findings highlight the importance of careful material development and contextual adaptation when designing school-based educational activities related to One Health. Further research is needed to formally assess their effects on educational outcomes, knowledge retention, and behavioural change.